2020
DOI: 10.1186/s10086-020-01857-4
|View full text |Cite
|
Sign up to set email alerts
|

The load factor in bolted timber joints under external tensile loads

Abstract: These experiments sought to empirically determine how the initial tightening force influences the ratio of the axial bolt force to the tensile load (load factor) and the load required to separate the joint interface (interface separation load) in tensile bolted joints of glued laminated timber. Load factor decreases with increasing initial tightening force; however, this tendency is reduced the greater the washer-member-end distance. In addition, tensile stiffness increases with decreasing load factor, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, recent research has reported that, when bolts are tightened to reach the plastic region of wood and are tightened in the direction of the grain of wood and wood-based materials, a high axial force is maintained over a long period of time, even if subjected to the effects of repeated drying and wetting [4,5]. Research and development regarding wood friction connectors and prestressed timber joints that utilize this axial force is currently underway and the authors have reported on the high seismic performance of bearing walls incorporating wood friction connectors and the joint performance of prestressed timber joints [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has reported that, when bolts are tightened to reach the plastic region of wood and are tightened in the direction of the grain of wood and wood-based materials, a high axial force is maintained over a long period of time, even if subjected to the effects of repeated drying and wetting [4,5]. Research and development regarding wood friction connectors and prestressed timber joints that utilize this axial force is currently underway and the authors have reported on the high seismic performance of bearing walls incorporating wood friction connectors and the joint performance of prestressed timber joints [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%